Climate Information Services, Climate-Smart Agriculture, and Farmer Adaptation in Zambia - Moyo, M.; Mpofu, N.; Dube, T.; Mutenje, M.; Kakwasha, K. (2025)
Climate change is posing risks to rain-fed agriculture in Zambia, necessitating timely and reliable Climate Information Services (CIS) to enhance farmer preparedness. This study evaluates the effectiveness of CIS in improving maize productivity among smallholder farmers, using data from 1,356 households across nine districts under the AICCRA programme. A mixed-methods approach was employed, combining household surveys and focus group discussions. Propensity Score Matching (PSM) was used to evaluate the effects of access to CIS on yield for maize. Results show that forecasts for rainfall onset and seasonal conditions were the most accessed and used CIS types, leading to early planting and variety selection. However, uptake of advice related to pest outbreaks and extreme events remained low due to financial constraints, late dissemination, and limited trust. Gender disparities were evident, with male household heads accessing CIS more than spouses or children. The study concludes that CIS access positively influences preparedness and adaptive practices, but effectiveness is shaped by socio-economic factors. It recommends strengthening CIS delivery through inclusive communication channels, timely dissemination, and integration with extension services and financial support mechanisms to improve uptake and impact.